Analisis Kinerja Aparatur Pemerintah Terhadap Pelayanan Pengaduan Masyarakat Berbasis E-Government Di Kota Bogor - irsalina, Nadira; Argenti, Gili; Febriantin, Kariena (Universitas Muhammadiyah Sumatera Utara, 2024)
This research aims to find out and analyze the performance of government officials regarding e-government-based public complaint services in Bogor City in implementing the SiBadra application in the Bogor City Communication and Information Service. This research uses a descriptive method with a qualitative approach. The research results show that: 1) In terms of productivity, Bogor City Diskominfo, as the person responsible, already has standard operating procedures. If there is still no response, the mayor will immediately take action against the OPD. Because Sibadra itself has been regulated in the guardianship and has become a Bogor City Government program. 2) The quality of service at Sibadra has been quite good, and we are always trying to make improvements. Sibadra itself has a WhatsApp service, so it could be easier. There is no longer any reason for people not to use this service. Apart from that, it takes up to 2x24 hours to produce a public report. 3). Sibadra's services continue to improve from year to year; this includes transparency of Sibadra website reports, to see reports that have been received and resolved. 4). From the side of the Sibadra team itself, there has been cooperation; the form of cooperation itself is in the form of solving problems or complaints from the community.Keywords: Apparatus Performance, E-Government, Community Complaints, SiBadra Application, Bogor City.